The effect of a sexuality training programme on the knowledge and attitudes of caregivers working with women with intellectual disabilities who live in residential care facilities : a social story approach - Bornman, Juan, 1968- (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.